Worms and human disease - Muller, Ralph, 1933- (CABI, 2002)
This book contains nine chapters on worms and human diseases. The book is written for physicians and medical technologists as a practical guide in human helminthology and for microbiologists, undergraduate and postgraduate students as an accessory text and a reference source. This is the second edition of Worms and Disease: A Manual of Medical Helminthology published in 1975. Topics covered are: trematodes; cestodes; Acanthocephala; Nematomorpha; nematodes; non-helminth groups; immunology of helminths; epidemiological aspects of helminth infections; helminthological techniques.